2020
DOI: 10.1007/s00223-019-00654-6
|View full text |Cite|
|
Sign up to set email alerts
|

BMP2 Modified by the m6A Demethylation Enzyme ALKBH5 in the Ossification of the Ligamentum Flavum Through the AKT Signaling Pathway

Abstract: Ossification of the ligamentum flavum (OLF) is characterized by a process of ectopic bone formation in the ligamentum flavum. The definitive pathophysiology of OLF still remains unclear, but the epigenetic m 6 A modification plays an important role in OLF. In addition, no studies have reported the function of ALKBH5 in OLF development. In this study, we investigated the function of the m 6 A demethylation enzyme ALKBH5 in OLF. To evaluate the function of ALKBH5, OLF tissues and normal ligamentum flavum tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…ALKBH5 was increased in ossification of the ligamentum flavum (OLF) tissues, and promoted the ossification of the ligamentum flavum cells through BMP2 demethylation and activating AKT signaling pathway [14]. The METTL3-mediated m6A methylation was found to be dynamically reversed by the demethylase ALKBH5, which acted to reverse the suppression of METTL3 in osteogenic progression, partly though regulating expression of MYD88 and facilitating the activation of NF-κB which was a well-known repressor of osteogenesis [28].…”
Section: Alkbh5 In Ossificationmentioning
confidence: 99%
See 2 more Smart Citations
“…ALKBH5 was increased in ossification of the ligamentum flavum (OLF) tissues, and promoted the ossification of the ligamentum flavum cells through BMP2 demethylation and activating AKT signaling pathway [14]. The METTL3-mediated m6A methylation was found to be dynamically reversed by the demethylase ALKBH5, which acted to reverse the suppression of METTL3 in osteogenic progression, partly though regulating expression of MYD88 and facilitating the activation of NF-κB which was a well-known repressor of osteogenesis [28].…”
Section: Alkbh5 In Ossificationmentioning
confidence: 99%
“…For example, ALKBH5 acted to influence spermatogenesis and trophoblast invasion, thus affecting human reproductive system diseases [23,29]. In addition, ALKBH5 also played an important role in the ossification of the ligamentum flavum cells and osteogenic progression via some famous signaling pathways, such as AKT and NF-κB signaling pathway [14,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, signaling associated with multiple cancers is dysregulated in PAAD development. We found that in patients with PAAD, a high ALKBH5 mRNA expression level was associated with the activation of AKT signaling pathways, which participate in important cellular pathological processes in PAAD development [27], suggesting that the mRNAs of molecules in the AKT pathway may be the m6a modi cation target mediated by ALKBH5 [28]. Recently, a study has shown that ALKBH5 functions as an anti-tumor protein in pancreatic cancer progression [29]; in this paper, upregulated ALKBH5 sensitized pancreatic cancer to gemcitabine-chemotherapy, and knockdown of ALKBH5 decreased pancreatic cancer cell invasion, migration, proliferation, metastasis, and tumorigenesis.…”
Section: Discussionmentioning
confidence: 90%
“…Additionally, signaling associated with multiple cancers is dysregulated in PAAD development. We found that in patients with PAAD, a high ALKBH5 mRNA expression level was associated with the activation of AKT signaling pathways, which participate in important cellular pathological processes in PAAD development [ 27 ], suggesting that the mRNAs of molecules in the AKT pathway may be the m6a modification target mediated by ALKBH5 [ 28 ]. Recently, a study has shown that ALKBH5 functions as an antitumor protein in pancreatic cancer progression [ 29 ]; in this paper, upregulated ALKBH5 sensitized pancreatic cancer to gemcitabine chemotherapy, and knockdown of ALKBH5 decreased pancreatic cancer cell invasion, migration, proliferation, metastasis, and tumorigenesis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%